I Want To Be A Vase - Torres, Julio (Comedian); Glander, Julian (New York : Atheneum Books for Young Readers, 2022)
An ambitious toilet plunger expresses his desire to be a vase.
new kids book 2022 summer.
Ages 4-8.
Grades K-1.
Keywords: Choice -- Fiction; Identity -- Fiction; Tools -- Fiction; House furnishings -- Fiction; Picture books